Saad bin Abi Waqqas, his biography and his position on the Rightly-Guided Caliphs and Muawiyah bin Abi Sufyan - Al-Yasiri, Ass prof . Kholoud H. Kamel (Thi Qar Arts Journal, 2022)
Saad bin Abi Waqqas is considered one of the important personalities and worthy of research for a number of reasons, such as his early Islam, his military role, and his political stances, as well as the kinship relationship between the Prophet Muhammad (PBUH) and Saad. Some of them praised his heroism, while others described him as cowardice, and some of them considered him to be among the scholars of the Companions and their ascetics, while others accused him of treason and negligence because of what he left after his death of money. Ali (peace be upon him) did not refrain from mentioning his virtues, but rather he declared them despite the authority’s prohibition from mentioning them at the time. All these and other matters prompted me to research Saad’s personality and his positions.